Investigation of Gait Characteristics and Factors Affecting Gait in Children with Atopic Dermatitis - Sarikurt, Furkan; Demir, Betul; Akgol, Gurkan; Kirik, Serkan; Cicek, Demet; Gural, Yunus (Galenos Publ House, 2024)
Aim: Atopic dermatitis (AD) is a chronic inflammatory disease. This study aimed to investigate gait characteristics and possible factors affecting gait in children with AD using Win-Track gait analysis. Materials and Methods: A total of 100 children, including 50 patients with AD, were diagnosed according to Hanifin Rajka criteria and 50 controls aged 7-16 years in this study. The Scoring of Atopic Dermatitis (SCORAD) index was calculated, and the body mass index (BMI) was determined. Serum immunoglobulin E (IgE), vitamin B12, and vitamin D levels were examined, and Win-Track gait analysis was performed. Results: Among the gait parameters, the median (minimum-maximum) maximum foot pressure on the left was 625.00 (412-872) in patients and 686.50 (466-890) in the controls (P = 0.006). The median step length on the right was 527.00 (258-640) in patients and 555.00 (422-672) in the controls (P = 0.012 ). Angle on the right was higher on the right side 7-11 age median 3.67 (1.49-11.31) compared to the 12-16 age median 1.51 (0-3.5) in those with moderate and severe SCORAD index (P < 0.05). Conclusion: Low foot pressure on the non-dominant limb side and short stride length on the dominant limb side were determined in patients with AD a gait characteristic different from those of controls. Gait parameters were found to be affected by increased disease severity, BMI, serum IgE, and vitamin D levels in patients with AD.
Keywords: Atopic dermatitis; gait; SCORAD; win-track